1998
DOI: 10.1210/jcem.83.2.4538
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with Propylthiouracil But Not Methimazole Reduces the Therapeutic Efficacy of Iodine-131 in Hyperthyroidism

Abstract: Ninety-three hyperthyroid patients were treated with 1 dose of iodine-131 (131I) during the past 10 years. Thirty-three were pretreated with propylthiouracil (PTU), 22 with methimazole (MMI), and 38 received no antithyroid drugs (ATD). ATD were discontinued 5-55 days before 131I therapy in three fourths of the cases and more than 4 months before therapy in one fourth of the cases. The frequency of cures in the 3 groups, 6-8 months after radioiodine therapy, was retrospectively studied. The cure rate among thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1
7

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(32 citation statements)
references
References 12 publications
0
24
1
7
Order By: Relevance
“…It is more than likely that patients with the mildest degrees of hyperthyroidism initially were over-represented in the group receiving no adjunctive antithyroid drugs. In the most recent retrospective studies, the radioprotective effect of propylthiouracil was shown to persist for at least 7 days (48,49), and as long as 55 days (50).…”
Section: Propylthiouracilmentioning
confidence: 99%
“…It is more than likely that patients with the mildest degrees of hyperthyroidism initially were over-represented in the group receiving no adjunctive antithyroid drugs. In the most recent retrospective studies, the radioprotective effect of propylthiouracil was shown to persist for at least 7 days (48,49), and as long as 55 days (50).…”
Section: Propylthiouracilmentioning
confidence: 99%
“…Embora o efeito do 131 I na oftalmopatia ainda seja controverso, estudos recentes, bem conduzidos, sugerem que a piora da oftalmopatia relacionada ao tratamento é transitória e pode ser prevenida pelo uso concomitante de glicocórticoides (63). O tratamento com 131 I apresenta como principal efeito colateral uma alta incidência de hipotireoidismo permanente, cuja freqüência no primeiro ano de tratamento varia de acordo com a dose de 131 I administrada (64), enquanto que a incidência posterior (3% ao ano) depende de fatores imunológicos (65), da associação ou não com drogas antitireoidianas (66), tamanho do bócio (67), radiosensibilidade individual, homogeneidade da distribuição de iodo na glândula tireóide e duração do seguimento dos pacientes tratados (68). Hipotireoidismo transitório pode ocorrer no período de 2 a 5 meses após o uso do radioisótopo (9-58% dos casos) (69).…”
Section: Iodo Radioativo Iodo Radioativounclassified
“…Despite its efficacy, radioiodine therapy (RAIT) fails in 10-50% of cases (4). The success of RAIT is influenced by many variables, including gender, age, thyroid volume, prior use of antithyroid drugs and baseline free thyroxine (FT4) levels; however, none of these variables reliably predict the outcome after RAIT (5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%